2020
DOI: 10.3389/fonc.2019.01542
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of lncRNAs in the Formation and Progression of Colorectal Cancer

Abstract: Colorectal cancer (CRC) is the primary cause of cancer-related death worldwide; however, specific and sensitive tools for the early diagnosis and targeted therapy of CRC are currently lacking. High-throughput sequencing technology revealed that gene expression of long-chain non-coding RNAs (lncRNAs) in a number of cancers directly or indirectly interferes with various biological processes. Emerging evidence suggests that lncRNAs regulate target genes and play an important role in the biological processes of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 117 publications
0
33
0
Order By: Relevance
“…Previous evidences indicate that ncRNAs could play a critical role in the regulation of cellular processes such as cell growth, apoptosis, and cancer progression and metastasis in colorectal cancer [11,12]. The combination of Pivot and survival analysis detected the ncRNAs which regulated crosstalk modules across the stages of COAD.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Previous evidences indicate that ncRNAs could play a critical role in the regulation of cellular processes such as cell growth, apoptosis, and cancer progression and metastasis in colorectal cancer [11,12]. The combination of Pivot and survival analysis detected the ncRNAs which regulated crosstalk modules across the stages of COAD.…”
Section: Discussionmentioning
confidence: 97%
“…Given the high incidence of global COAD cases and increased mortality due to distant metastasis, it is of paramount importance to identify the novel regulatory pathways involved in COAD growth and metastasis. In recent years, a growing amount of research has shown that not only some important genes but also ncRNAs play key roles in the process of COAD progression [11,12]. Presently, most of the researches only focus on certain gene families or miRNA families [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent researches have indicated that many lncRNAs exert an important role in almost all physiological and pathological processes, including embryonic stem cell, carcinogenesis, and cancer metastasis. 3,4 The lncRNAs have been reported to function as oncogenes or tumor suppressor gene, participating in CRC tumorigenesis and progression. For example, a report from Xu et al showed that lncRNA MIR17HG drove tumor development and metastasis in colorectal cancer cells via enhancing the expression of NF-κB/RELA.…”
Section: Introductionmentioning
confidence: 99%